(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2017)
Efficiency of financial and economic activity of an enterprise is impossible without realization of measures of realization of innovative activity. An analysis of the innovation activity of an enterprise requires a systematic approach that is possible with the involvement of the appropriate valuation-analytical toolkit. In particular, the interaction of elements of the innovation potential of an enterprise can be characterized by indicators of elasticity, profitability, susceptibility, activity. The purpose of the article is to develop methodological support for analysis and evaluation of innovative activity of enterprises, taking into account the systemic interaction of elements of innovation activity. In the article a set of indicators of the analysis of innovation activity is complemented by the indicator of synergistic interaction of the elements of the innovation system of the enterprise, and on this basis is formed the method of evaluation and analysis of the innovative activity of the enterprise, which takes into account synergistic interaction and nonlinearity of innovation processes. The scenario variants of synergistic interaction have been worked out and the corresponding innovative strategies have been proposed. The proposed method allows to identify and engage management and organizational factors in the development of innovation activities. Their use always increases in the conditions of the economic crisis, as the effect of organizational and managerial innovations (systemic effect) can be quite high at relatively low costs for their implementation. Therefore, their relevance in today’s crisis is increasing, as their role in supporting innovation in reducing investment, which is due to the crisis, is increasing. The use of the proposed aggregated methodology for assessing and analyzing the innovation activity of an enterprise can increase the adequacy of information that will be used when making decisions by the management of the enterprise, and also significantly reduces the period from the occurrence of the problem to the decision on its elimination compared with standard systems of evaluation and analysis of innovation activity. In addition, the proposed methodology for evaluating and analyzing the company’s innovative development allows for synergistic flows to be taken into account in the innovation environment of the enterprise and their impact on the innovative development of the enterprise.